CHARACTERISTICS OF TOP MANAGEMENT, AUDIT QUALITY, AND EARNINGS MANAGEMENT IN INFRASTRUCTURE COMPANIES - Nainggolan, Abdullah; Choiriah, Siti (Unversitas Prof. Dr. Moestopo (Beragama), 2026)
Financial statements serve as a medium for communicating information regarding various economic events and transactions, including operating performance, financial position, changes in financial position, changes in equity, and corporate cash flows. One of the key pieces of information presented in financial statements is corporate earnings. Earnings are often utilized as an instrument to enhance the appearance of financial reports in order to portray improved company performance. Consequently, earnings management practices are frequently employed to present financial information that does not fully reflect the firm’s actual condition. This study aims to analyze the effect of top management characteristics on earnings management, with audit quality serving as a moderating variable. The research population consists of 67 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected using a purposive sampling technique, resulting in 55 companies that met the criteria and yielding 275 observations over five years. Data were obtained from the companies’ annual reports and analyzed using Moderated Regression Analysis (MRA) based on panel data with the assistance of EViews 10 software. The results indicate that top management knowledge and tenure do not empirically demonstrate a negative and significant effect on earnings management. Audit quality is empirically proven to moderate the relationship between top management knowledge and earnings management practices. However, audit quality does not moderate the relationship between management tenure and earnings management practices in infrastructure companies listed on the Indonesia Stock Exchang.